Peran Kepatuhan Wajib Pajak dalam Memediasi Pengaruh Digitalisasi Sistem Perpajakan terhadap Pendapatan Pajak Daerah Kota Bekasi Tahun 2026 - Yusuf, Daud; Evi Nausta Pardede, Tiolina (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of local tax system digitalization, including accessibility, system integration, and payment methods, on local tax revenue for individual taxpayers in Bekasi City in 2026, as well as to examine the role of taxpayer compliance as an intervening variable. The study population consists of all active PBB-P2 taxpayers in Bekasi City, totaling 713,881 taxpayers, with a sample of 200 respondents selected using accidental sampling. Data were collected through a closed-ended questionnaire using a 1–5 Likert scale. The analysis was conducted using descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. The results indicate that digital system accessibility facilitates taxpayers in fulfilling their obligations, system integration enhances administrative efficiency and supervision, and efficient and practical payment methods encourage higher compliance, which collectively contributes to increased local tax revenue. Taxpayer compliance also serves as a mediator, indirectly influencing the relationship between digitalization and tax revenue. These findings provide a basis for developing more responsive, transparent, and user-friendly digital tax services in Bekasi City.